Animal-based medicines used in ethnoveterinary practices in the semi-arid region of Northeastern Brazil - Souto,Wedson M.S. (2012)
This work documents the zootherapeutic practices in Ethnoveterinary medicine (EVM) of Pedra Lavrada (6°45'S, 36°28'W), Northeastern Brazil. We interviewed 23 people (22 men and 1 woman), who provided information on animal species used as remedies, body parts used to prepare the remedies, and illnesses for which the remedies were prescribed. We calculated the use-value to determine the most important species. Interviewees cited 11 animal taxa. The main species mentioned were ram - Ovis aries (UV=0.89), crab-eating fox - Cerdocyon thous (UV=0.79), common green iguana - Iguana iguana (UV=0.79), and South American rattlesnake - Caudisona durissa (Linnaeus, 1758) (UV=0.74). The most frequently cited treatments concerned to inflammatory and dermatological ailments or conditions, as well as to obstetric disorders. Similar to other studies, local ethnoveterinary establishes connections with human ethnomedicine. The results suggest that similarities in the repertoire of medicinal resources chosen by local residents reflect the local accessibility/availability of the resources. Our results help to preserve ethnoveterinary knowledge, which is important in enhancing our understanding on the relationship among humans, society and nature, and also to elaborate more effective strategies for conserving natural resources. Other studies for scientific validation of the effects and side effects of these zootherapeutic products are needed before they can be recommended or not for use.